Interdependent intermetallic compound growth in an electroless Ni-P/Sn-3.5Ag reaction couple - Kumar, Aditya (2013)
The interfacial microstructure of electroless Ni-P/Sn-3.5Ag solder joints was investigated after reflow and high-temperature solid-state aging to understand its interdependent growth mechanism and related kinetics of intermetallic compounds (IMCs) at the interface. The reflow and aging results showed that mainly three IMC layers, Ni3Sn4, Ni2SnP, and Ni3P, formed during the soldering reaction. It was found that the Ni3Sn4 and Ni3P layers grow predominantly as long as the electroless Ni-P layer is present; however, once the Ni-P layer is fully consumed, the Ni2SnP layer grows rapidly at the expense of the Ni3P layer. A transition in the Ni3Sn4 morphology from needle and chunky shape to scallop shape was observed after the solid-state aging of reflowed samples. The kinetics data obtained from the growth of compound layers in the aged samples revealed that initially the growth of the Ni2SnP layer is controlled by diffusion, and subsequently by the rate of reaction after the Ni-P metallization is fully consumed. It was found that complete transformation of the electroless Ni-P layer into a Ni3P layer results in the rapid growth of the Ni2SnP layer due to the dominating reaction of Sn with Ni3P. The apparent activation energies for the growth of Ni3Sn4, Ni2SnP, and Ni3P compound layers were found to be 98.9 kJ/mol, 42.2 kJ/mol, and 94.3 kJ/mol, respectively.